THE IMPORTANCE OF DRAMA IN TEACHING FOREIGN LANGUAGES - Davlatova, Gulkhayo Kosimovna (INTERNATIONAL CONFERENCES, 2022)
There are ample approaches, methods and technics in the procedure of teaching foreign languages. However, making a choice an appropriate process (three notions are meant as a unit) is a bit daunting task to conduct the lesson. Therefore, it is going to be covered an idea of using drama in the classroom and ways to utilize this method successfully to teach an unfamiliar language.